Designing and Manufacturing a Goalie Mask (Hungarian Journal of Industry and Chemistry, 2010)
At the present time the composite materials are used in many areas of industry. The main utilizations are in the aircraft industry and the sports equipment manufacturing. The first part of the work offers on overwiew of composite materials, their properties and utilize. The next part introduces the evolution of goalie masks. In the main part, we used the knowledge from the previous chapters, and designed a new shape of the mask and produced a prototype model. The backplate was designed by 3D CAD software and the form was produced on NC milling machine. For the production of the mask I used technology of laminating and remark two possible solutions as production forms and prototype models.
Keywords: composite materials; hockey goalie mask; CNC milling; laminating